Iron Oxide Doped Spray Dried Aluminum Oxide Granules for Selective Laser Sintering and Melting of Ceramic Parts. Issue 6 (6th March 2019) - Pfeiffer, Stefan; Florio, Kevin; Makowska, Malgorzata; Ferreira Sanchez, Dario; Van Swygenhoven, Helena; Aneziris, Christos G.; Wegener, Konrad; Graule, Thomas
Abstract : Powder bed density, flowability, and laser light absorption of the powder strongly influence the quality and performance of aluminum oxide parts processed by selective laser sintering and melting. By means of spray drying, highly dense granules with a good flowability are manufactured. An ultrasonic atomizer and a co‐current droplet air mixing are used to spray aqueous slurries consisting of either bimodal or trimodal distributions of aluminum oxide. Nano‐iron oxide improves the interaction with the green pulsed laser. The improved absorption of the green laser light is verified by means of an Ulbricht sphere. The appropriate amount of dispersant for consecutive water‐based spray granulation is determined by Zeta Potential measurements. Dibasic ammonium citrate is found to be the most suitable dispersant. A final uniform distribution of the iron oxide within the spray dried granules is confirmed by X‐ray μ‐beam fluorescence tomography. The powder quality is characterized by apparent density, tapped density, Hausner ratio, moisture content, and particle size distribution. Powders with a tapped density of almost 50% of the theoretical density and an absorbance of 69% (green laser light) lead to maximum densities of the laser processed parts of around 96%. Abstract : Powder properties and laser light absorption strongly influence aluminium oxide parts processed by SLS/SLM. By means of spray drying, granules are manufactured to solve these problems. Nano‐iron oxide is implemented uniformly to improve the interaction with the used laser. This is verified by X‐ray m‐beam fluorescence tomography. Powders with high density and high absorbance lead to dense SLS/SLM processed parts.